The black stork : eugenics and the death of "defective" babies in American medicine and motion pictures since 1915 - Pernick, Martin S. (Oxford University Press, 1996)
In the late 1910s Dr. Harry J. Haiselden, a prominent Chicago surgeon, electrified the nation by allowing the deaths of at least six infants he diagnosed as "defectives." Seeking to publicize his efforts to eliminate the "unfit," he displayed the dying infants to journalists, wrote about them for the Hearst newspapers, and starred in a feature film about his crusade. Prominent Americans from Clarence Darrow to Helen Keller rallied to his support.